Understanding risk factors and microbial trends implicated in the development of Whipple-related surgical-site infections. Issue 1 (1st March 2023) - Feng, Wendy; Irfan, Ahmer; Fleece, Molly; Dudeja, Vikas; Reddy, Sushanth; Hashmi, Salila; Rose, J. Bart; Lee, Rachael A.
Abstract: Objective: The purpose of this study is to understand the role of risk factors and postoperative complications seen in patients undergoing Whipple procedures in the development of surgical site infections. Our secondary goal was to evaluate whether microbial patterns differed between preoperative antibiotic classes, offering insight into the effectiveness of current practices while promoting antibiotic stewardship. Design: We performed a retrospective cohort study comparing patients with and without SSIs. Setting: This study was conducted at a tertiary-care center in the southeastern United States. Participants: Patients who underwent a Whipple procedure between 2012 and 2021 were acquired from the National Surgical Quality Improvement Program (NSQIP) database. Results: Patients with a bleeding disorder reported higher SSI rates ( P = .04), whereas patients with a biliary stent reported lower surgical site infection (SSI) rates ( P = .02) Those with postoperative complications had higher SSI rates, including delayed gastric emptying ( P < .001) and pancreatic fistula ( P < .001). Patients with longer operative times were 1.002 times more likely to develop SSIs (adjusted odds ratio [aOR], 1.002; 95% confidence interval [CI], 1.001–1.004; P = .006) whereas surgical indications for malignancy correlated with decreased SSIs risk (aOR, 0.578; 95% CI, 0.386–866) when adjusting for body mass index, surgical indication, and duration of surgical procedure. Conclusions: Optimizing preoperative management of modifiable risk factors for patients undergoing pancreatoduodenectomies and decreasing operative times may reduce SSI rates and patient and hospital burden. Further research is needed to understand whether stent placement reduces SSI risk in pancreatoduodenectomy.